(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
In the context of the accession of the Western Balkans to the EU, which geopolitical challenges have recently pushed to completion, the defence of fundamental European values and the institutional principles, that are their expression, is becoming increasingly urgent. A new commitment has emerged on the part of the European Union to reassert its unity and its responsiveness to welcome the new candidates, imposing a revision of the institutional system within which enlargement must take place. The eastward enlargement of 2004-2005, based on conditional rules, imposing respect for democracy and the rule of law, already revealed that the deepening of the EU’s constitutional set-up cannot be separated from the opening of the negotiations with potential new members. Indeed, the absence of clear rules governing the entry of new States, which would, for their part, undertake to respect the obligations arising from European law, on the one hand, and the presence of an incomplete apparatus of sanctions for cases of violation of these obligations, on the other hand, would impede the orderly development of the integration process. As will be seen, reaffirming that respect for fundamental values within the meaning of Article 2 TEU constitutes a primary, non-negotiable and mandatory obligation, especially at the time of enlargement, is of absolute importance, and it is equally important that this obligation be promptly guaranteed by political and jurisdictional remedies of a punitive nature. On the contrary, a disengagement on such issue would undermine the credibility of the European project whose historical and ideological significance is based on an identity common to European nations.